2017
DOI: 10.3168/jds.2016-12458
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters of blood β-hydroxybutyrate predicted from milk infrared spectra and clinical ketosis, and their associations with milk production traits in Norwegian Red cows

Abstract: The aim of this study was to estimate genetic parameters for blood β-hydroxybutyrate (BHB) predicted from milk spectra and for clinical ketosis (KET), and to examine genetic association of blood BHB with KET and milk production traits (milk, fat, protein, and lactose yields, and milk fat, protein, and lactose contents). Data on milk traits, KET, and milk spectra were obtained from the Norwegian Dairy Herd Recording System with legal permission from TINE SA (Ås, Norway), the Norwegian Dairy Association that man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
38
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 22 publications
11
38
1
Order By: Relevance
“…The mean of the marginal posterior distribution of estimates suggests a small additive genetic influence on serum albumin concentrations, whereas total proteins, globulins, and the A:G exhibited moderate heritability (~0.20), in line with other studies that have revealed the existence of genetic variation for blood constituents (e.g., albumin, globulin fractions, total protein; Rowlands et al, 1974;Jensen and Christensen, 1975;Peterson et al, 1982). Blood BHB was instead found to have relatively high heritability (0.37), although it was in the range of published values (Oikonomou et al, 2008;van der Drift et al, 2012b;Belay et al, 2017b). This result indicates that it may be possible to select cows with lower blood BHB, although, considering the nature of the trait, it is clear that more accurate estimates might be obtained by focusing on early lactation.…”
Section: Genetic and Herd-date Variation In The Spp And In Bhbsupporting
confidence: 85%
See 2 more Smart Citations
“…The mean of the marginal posterior distribution of estimates suggests a small additive genetic influence on serum albumin concentrations, whereas total proteins, globulins, and the A:G exhibited moderate heritability (~0.20), in line with other studies that have revealed the existence of genetic variation for blood constituents (e.g., albumin, globulin fractions, total protein; Rowlands et al, 1974;Jensen and Christensen, 1975;Peterson et al, 1982). Blood BHB was instead found to have relatively high heritability (0.37), although it was in the range of published values (Oikonomou et al, 2008;van der Drift et al, 2012b;Belay et al, 2017b). This result indicates that it may be possible to select cows with lower blood BHB, although, considering the nature of the trait, it is clear that more accurate estimates might be obtained by focusing on early lactation.…”
Section: Genetic and Herd-date Variation In The Spp And In Bhbsupporting
confidence: 85%
“…Estimates of the additive genetic correlations for BHB and udder health traits, milk production traits, and milk coagulation properties are presented in Table 4. A positive genetic correlation was found between BHB and milk yield (0.716), even if higher than previous findings (Belay et al, 2017b). This was expected because selection for high milk production has resulted in an increased risk of NEB and greater body fat mobilization (Veerkamp et al, 2003;Coffey et al, 2004).…”
Section: Genetic and Environmental Relationships Between Bhb And Uddementioning
confidence: 54%
See 1 more Smart Citation
“…These predictions may, however, be considered accurate enough to employ in genomic evaluations, as described by Bastin et al (2016) and Bonfatti et al (2017). The accuracy of our MIR prediction of serum BHB was better than that of Belay et al (2017b), who used MIR predictions of serum BHB to investigate the genetic parameters of ketosis and the genetic relationships between serum BHB concentration and milk production traits. Similarly, our MIR prediction of serum fatty acids concentration had comparable accuracy to the MIR prediction of energy balance reported by McParland et al (2015), who found favorable correlations between MIR-predicted and measured energy balance.…”
Section: Pls Regression Models For Predicting Serum Metabolite Concenmentioning
confidence: 89%
“…Most research and industry applications using milk FTIR data focus on developing prediction equations for economically important phenotypes such as fine milk composition (Rutten et al, 2010(Rutten et al, , 2011Fleming et al, 2017aFleming et al, ,b, 2018 and technological properties of milk (Cecchinato et al, 2009. In addition, FTIR data have been shown to be a potentially valuable tool for predicting health and reproductive phenotypes (Heuer et al, 2001;Belay et al, 2017;Toledo-Alvarado et al, 2018) and for predicting residual feed intake, DMI, and methane emissions (Shetty et al, 2017a,b;Bittante and Cipolat-Gotet, 2018;Dórea et al, 2018).…”
Section: Introductionmentioning
confidence: 99%